Biotechnology in Healthcare, Volume 1: Technologies and Innovations - Barh MSc, MTech (Elsevier Science & Technology, 2022)
Biotechnology in Healthcare, Technologies and Innovations, Volume One presents up-to-date knowledge on the emerging field of biotechnology as applied to the healthcare industry. Sections cover 3D printing, tissue engineering, synthetic biology, nano-biotechnology, omics, precision medicine, gene therapy, vaccine development, predictive healthcare, entrepreneurship, financing, business models, product development and marketing in the sector. This is a valuable source for biotechnologists, bioinformaticians, clinicians and members of biomedical and healthcare fields who need to understand more about the promising developments of the emerging field of biotechnology in healthcare.